When we were brilliant - Cullen, Lynn (Berkley, 2026)
"They were an unlikely pair--a blond bombshell and hawkish photographer--but Marilyn Monroe and Eve Arnold would make a deal that would change their lives in this dazzling new novel from national bestselling author Lynn Cullen. In 1951, Norma Jeane Baker follows documentary photographer Eve Arnold into a powder room, the first night they meet. She has a proposition for her: Norma Jean built Marilyn Monroe to be photographed, and she wants Eve to do it. Eve, who is better than anyone she's seen at capturing beauty, at shedding light on her subjects. Together, they can help each other. Together, she says, they can make something brilliant. Skeptical of this cipher of a young woman, Eve demurs. But she keeps getting drawn back into Marilyn's orbit. Until the women come to recognize something in each other, something fundamental. Nothing will get in the way of what they want, and when Marilyn's star takes off to teetering heights, neither will ever be the same. A lavish and transporting novel, When We Were Brilliant captures the halcyon days of an icon and the grit of women determining their own futures as it explores the exceptional and complicated friendship between Marilyn Monroe and Eve Arnold"-- Provided by publisher.